Lola Reyes is so not worried - Rodriguez, Cindy L., 1971- (Harper, an imprint of HarperCollins Publishers, 2024)
Lola Reyes doesn't want to leave Guatemala, a place full of warmth and sun, laughter and music--where her abuela and prima and tíos and tías surround her with love. Back in Sunnyside, it's cold. There's schoolwork and chores. And her mama transforms into Lola's super-serious school principal, Dr. Reyes. Back at home... Lola can see, crystal clear, the empty place where Pop used to be. So Lola decides to bring a little bit of Guatemala--and Pop--back with her. She discovers his box of childhood worry dolls and sneaks them into her luggage, ignoring the warnings on the box not to use them. Later, when she tells them all her worries, from her friendship woes to the way Mama won't talk about how sad she is, the worry dolls come to life! Worse--they escape! Lola has to enlist her neighbor and nemesis, Chance Townsend, to recapture the dolls because she discovers they're cursed! And as they absorb worries, they'll grow bigger and bigger. If Lola can't find a way to stop them, they'll burst, releasing all the worries they've absorbed a hundredfold on everyone in town! But when breaking the curse might mean confronting her own anxieties and grief, will Lola be able face her emotions before it's too late?